Changing the Minds of Skeptics : How Strategic Communications Can Build Momentum for Tax Reform - Rahman, Shaela (World Bank, Washington, DC, 2012)
The project, a joint initiative of the investment climate department and International Finance Corporation (IFC) advisory services in the Middle East and North Africa, was launched in response to the Yemeni government's request for assistance with tax reform, a central part of its broad reform plan. The 18-month first phase, which ended in June 2009, focused on the groundwork including process mapping, drafting of the income tax law, a compliance cost survey, and so on, as well as preparation of a communications strategy to support the work of second phase, which just began in FY10.